Didactic materials and resources for english classes: Useful strategies for improving the english teaching process at the Luis Carlos López institution (2019)
The purpose of this paper is to share and describe the results of a meaningful experience project that aimed to propose didactic strategies towards the lack of materials and resources in English for third grade courses at the Institution Luis Carlos Lopez, Cartagena, Colombia. The inappropriate adequacy of an English learning environment and the lack of didactic materials for English classes may suppose a big challenge for teachers who endure the few interest and participation of his/her students to the classes, especially in primary education. It was concluded that the use of didactic materials and resources in English offers a valuable strategy to motivate the students and regain their attention and interest to learn the language and to be active in the learning processes.